Dampak Teknologi Digital Terhadap Pertumbuhan Ekonomi - Arifin, Zainal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
Digital technology has become a major driver of global economic transformation, having a significant impact on productivity, innovation and the creation of new markets. This research aims to analyze how digital technology influences economic growth, both in terms of opportunities and challenges. Digitalization increases efficiency and productivity through automation, data analytics, and the development of new business models such as e-commerce and fintech. In addition, digital technology opens up global market access, accelerates innovation, and creates employment opportunities in technology-based sectors. However, workforce disruption due to automation, the digital divide, and regulatory challenges are the main obstacles that need to be overcome. Countries that are able to strategically integrate digital technology into their economies tend to experience faster economic growth than countries that lag behind in digital transformation.